The effect of ethno/lingo diversity on knowledge sharing in groups - Ziaei, Seyyed Ali; Md Nor, Khalil; Walczak, Steven (2010)
In today’s economy, the role and value of knowledge as the last competitive advantage has been suggested and the Knowledge Management (KM) concept has emerged and received great attention.A big part in KM is about managing the way knowledge flows in and between organizations i.e., managing Knowledge Sharing (KS).While technology admittedly facilitates KS, the success of KM efforts still depends highly on considering human factors.This paper proposes that one of these human factors, ethno/lingo diversity, can significantly affect the success of KM practices; in particular knowledge sharing by influencing communication and social interaction among the members of a group.An empirical investigation is suggested to test the proposition.